All nanocarbon Li-Ion capacitor with high energy and high power density. (June 2018) - Dubal, Deepak P.; Gomez-Romero, Pedro
Abstract: An energy storage device reaching energy densities of 102 Wh/Kg at power densities of 10 4 W/Kg would mean the possibility of charging such a device in 36 s. The nanocarbon device presented here is closer to that feat than any previously reported system. N-doped Carbon Nanopipes were used as anode and Partially Reduced Graphene Oxide as cathode, with LiPF6 EC/PC electrolyte. This system yields simultaneously high energy and power densities (262 at 450 W/kg and 78 Wh/kg at 9000 W/kg) which are energy/power combinations considerably higher than those of present Li-ion batteries. Our cell exhibits excellent cycle stability (∼91% capacity retention after 4000 cycles "0.01–4 V"). These breakthrough results are based on the kinetic balancing of the nanocarbon electrodes, which can deliver excellent high energy density at high rates and low costs. Graphical abstract: The complementary electrochemistries of two different but kinetically balanced nanocarbons (Carbon Nano-Pipes and Partially Reduced Graphene Oxide) (left) can be combined in a breakthrough Li-Ion Capacitor device (LIC) featuring simultaneously high specific power and energy (right). Highlights: Design of all Nanocarbon Li-ion capacitor. A novel pair of Nitrogen doped carbon nanopipes anode and partially reduced graphene oxide cathode. High Energy density of 262 Wh/kg with high power density of 9 kW/kg. Surpasses energy density of Supercapacitors and power density of Li-ion battery.